Temporary Performance Artist Communities:: The Case Model of the Venice International Performance Art Week - Pagnes (VestAndPage), Andrea (2022)
This article addresses the case model for the Live art exhibition project Venice International Performance Art Week, founded and curated by artist duo VestAndPage (Verena Stenke and Andrea Pagnes) in 2012. Since its inception, it has promoted performance art and Live art practices on a local, national, and international scale through live performance events, exhibitions, formative learning programs, and co-creation experiences. Founded on the principles of sustainability, hospitality, and care, it has become a recognized international platform where dialogue and exchange, artistic expressions and cultures can flourish proactively among performers. The project formats have evolved over the time, progressively focusing on forming temporary performance artist communities in terms of a social sculpture. Its core mission is to foster exchange among performers, Live artists, and people: a gathering reunion, a people’s project made by the people for the people. It functions as a think-tank for outlining conceptual visions which declaredly overcome imposed and external human conditioning, generating accretive reflection on topics such as poetic and civil sovereignty, inclusiveness, and accessibility through performance practices. As the project founders, we have also conceived it as a breeding ground for future professional opportunities of the participating artists, curators, and cultural operators, as well as a means to broaden the audience for performance art and Live art, both locally and internationally. The Venice International Performance Art Week has now adapted into an experiential co-creation artist-in-residence format. This enables to expand performance art and Live art beyond works of presentation and display, focusing instead on real time co-creation of interdisciplinary collective productions.